The Scales Of Justice: Evaluating Fairness In Pakistan’s Criminal Proceedings - Muhammad Qasim Arslan , Syed Adil Abbas Naqvi , Adina Farishta , Dr. Mazhar H . Bhutta (Migration Letters, 2024)
Purpose: This study investigate to explore the perceptions of the general public regarding the fairness of the criminal justice system Pakistan. Specifically, the study identifies the determinants that significantly influence one’s perception and measure the overall trust and satisfaction level toward legal representation among those having experience with criminal cases. Methods: Using a purposive sample of 150 respondents who have either professional or personal experience with the criminal justice system in Pakistan, the study collects quantitative data through a structured questionnaire. The study uses analytical tools such as descriptive statistics (Graphs & Frequency Distribution), correlatio[1]n analysis, and multivariate regression analysis, which is employed in SPSS, to examine and quantify the relationships. Results: The results show a significant polarization in respondents’ perception, with more than half of the respondents having a negative perception toward the criminal justice system while the rest have a positive perception. Individually, the economic influence, and quality of legal disputes have high positive correlation to their perceptions of the fairness and trust of the system. Conclusion: Based on the evidence, the results suggest the desire for a systematic reform that should involve more transparency, less economic influence, and better legal representation. These three in combination could increase perception of fairness of the criminal justice system in Pakistan, retain the lost trust, and create an environment of justice. The findings support evidence-based policy for better areas of the organ to enhance fairness and integrity.